Traffic video detection and monitoring - Dwekat, Mohammad; Hanani, Yazan; Shaer, Noor; Deryeh, Mohammad (My University, 2021)
In past few years, traffic accidents and traffic rules violations have increased at great extant, even in our everyday life we come across several problems caused due to traffic rule violation by someone. We also know that incidents are one of the big problems in our country. These problems consume our time and causes a disturbance in the system. This project will be designed in order to prevent this type of accidents from happening by detecting the violated car then system captures a photo of violating car and detect the license plate number then transfer the information of violation to a website which is a reference for the drivers, and the website sends an SMS message to the violator. Raspberry pi will be used to control the camera module, sensors, and to send the details of the violation to the database, then sends a notification to the violator. Website will be built using Java tools, HTML, CSS and PHP. which will be used to check the violations. GSM module used to send message to the violator. PHP will be used to send the command from the microcontroller to the database. And database designed to contain two tables the first has the information’s of the driver and the second one has the information’s of the violations. The project worked very well which has been tested to detect the violation vehicles and worked well in detecting the license plate number and giving the violation to that number.